Smart City Policy: Strategy and Implementation to Realize Smart Urban Governance in Indonesia - Sulistyaningsih, Tri; Purnama, Rika Ayu; Kulsum, Umi (Journal of Governance and Public Policy, 2023)
This paper elaborates on policies, strategies, and implementation of Smart Cities in Indonesia. Due to regulatory, strategy, and implementation problems for Smart City, there are still differences in understanding and strategy in its implementation. Smart urban governance is part of a smart city, so one strategy to implement smart urban governance is a smart city policy in Indonesia. There is a fragmentation of inconsistent approaches, policies, implementations, and strategies in practice. This research will develop arguments, analyze published articles and regulations, and map them out. The research method used was a qualitative approach. The data sources used were articles from Scopus which found 213 articles using the keywords smart city policies and smart urban governance and regulations, which were then processed using VOSviewer and Nvivo 12 Plus software. This study indicated that to implement smart urban governance in Indonesia, strategies such as the first need to be supported by the central government to make a policy regarding smart cities, including smart urban governance, followed by smart city policies in the towns in Indonesia. Second, there are technological developments that support the implementation of smart cities. Third, there are institutional and human resource factors, but these are still obstacles to implementing smart cities in Indonesia. Meanwhile, the urban issues developed in Indonesia are mega-urban in the big island, urban management and financing, housing for lower-income, sustainable urban infrastructure, and resilient disaster mitigation and management.